Dispensation of outpatient hospital medicines by hospital only versus hospital-community pharmacies collaboration: a cross-sectional study and survey of patient’s satisfaction - Ferrández, Olivia; Grau, Santiago; Colominas-González, Elena; Navarrete-Rouco, María Eugenia; Carballo-Martínez, Nuria; De Antonio-Cuscó, Marta; Fernández-Sala, Xènia; Rio-No, Laura; Fando Romera, Oscar; Berzosa Malagon, Maria; Pineda Rodriguez, Sergio; Torres Rius, Noelia; et al. (Frontiers in Public Health, 2024)
Goal To describe the experience of a dispensing model of outpatient hospital medicines (OHM) via collaboration of hospital and community pharmacies, and to explore patient satisfaction with the strategy as compared with the hospital pharmacy only service. Background Patient satisfaction is an important component of the quality of health care. Study A new model of dispensing OHM was conducted in the Outpatients Unit of the Service of Hospital Pharmacy of Hospital del Mar, in Barcelona, Spain. Participants were patients on stable chronic treatment with clinical or social fragility, immunocompromised patients, and those whose residence was located at a distance from the hospital that justified drug delivery through the community pharmacy. A cross sectional study was done using an ad hoc 14-item questionnaire collecting demographic data, duration of treatment, usual mode of collecting medication, and the degree of satisfaction regarding waiting time for the collection of medication, attention received by professionals, information received on treatment, and confidentiality. Results The study population included a total of 4,057 patients (66.8% men) with a mean age of 53 (15.5) years, of whom 1,286 responded, with a response rate of 31.7%. Variables significantly associated with response to the survey were age over 44 years, particularly the age segment of 55–64 years (odds ratio [OR] 2.51) and receiving OHM via the community pharmacy (OR 12.76). Patients in the community pharmacy group (n = 927) as compared with those in the hospital pharmacy group (n = 359) showed significantly higher percentages of ‘satisfied’ and ‘very satisfied’ (p < 0.001) in the waiting time for the collection of OHM (88.1% vs. 66%), attention received by professionals (92.5% vs. 86.1%), and information received on treatment (79.4% vs. 77.4%). In relation to confidentiality, results obtained were similar in both pharmacy settings. Conclusion Dispensing OHM through the community pharmacy was a strategy associated with greater patient satisfaction as compared with OHM collection at the hospital pharmacy service, with greater accessibility, mainly due to close distance to the patient’s home. The participation of community pharmacists could further optimize the care received by patients undergoing OHM treatment.